'My father is Muslim and my mother is Christian: What about me?' Religious identity and agency within mixed families in Morocco. (September 2022) - Therrien, Catherine
This article explores not only the narratives of mixed individuals regarding what has been transmitted to them by their parents in terms of religious background, but also their own religious practice and affiliation. More specifically, the article focuses on mixed individuals who were raised in Muslim–Christian practicing families and who have grown up in Morocco. I will argue that despite the constraints of the religious context and the fact that they were raised in an interreligious practicing family, they are nevertheless active agents in the formation of their religious identity. The context in which they lived impacts their daily life, but not their capacity to make their choices in terms of religious identity. They do not always feel free to display their choices socially, face social pressure to conform to the majority group religious norms and/or family expectations, but develop adaptive practices to socially navigate the different social and family contexts.